Memahami Toleransi Risiko Finansial di Kalangan Investor Muda - Arya Samudra Mahardhika; Yanuar Eko Restianto (Politeknik Ganesha Medan, 2023)
This study aims to empirically examine the effect of self-esteem and financial literacy on financial risk tolerance. In addition, this study also examines the relationship between financial risk tolerance and investment decisions. This type of research is quantitative causality with 68 respondents who were used as research samples through distributing questionnaires to investors in Kebumen Regency. The research hypothesis was tested using Structural Equation Modeling (SEM) with the help of WarpPLS version 8.0 software. The results of this study indicate that self-esteem has a positive effect on financial risk tolerance and financial risk tolerance has a positive effect on investment decisions. However, research cannot prove that financial literacy has an effect on financial risk tolerance. These findings indicate that investors in the current era tend to make stock investment decisions based solely on their perceptions, therefore, socialization and early education about stock investment is very important so that prospective investors can experience definite benefits from the stock investments they made.